Mining - Williams, Brian, 1943-; Morris, Tony (Austin, Tex. : Raintree Steck-Vaughn, 1993)
Discusses the history of mining, the various kinds of mines, mining around the world, and mining today and tomorrow.
Includes index.
Keywords: Mines and mineral resources -- Juvenile literature; Miners -- Juvenile literature; Minerals -- Juvenile literature; Mines and mineral resources